Degradable material for catering and preparation method thereof

Through the synergy between modified calcium carbonate, PBAT resin and PPCP resin, the problem of insufficient barrier properties and light transmittance of PBAT packaging film is solved, and a high barrier properties and light transmittance of catering degradable materials are achieved, thereby improving the packaging material performance and economic value.

CN119220061APending Publication Date: 2024-12-31陈丽春
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410960667.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The barrier properties and light transmittance of PBAT packaging film are not high, which affects its freshness and transparency as packaging material.

Method used

Using specific modified calcium carbonate to synergistically work with PBAT resin and PPCP resin, the preparation method of modified calcium carbonate includes reaction of calcium carbonate with nitric acid solution and sodium 3-mercaptopropane sulfonate, followed by acrylate monomers and The initiator is mixed to form a molecular chain interspersed structure to improve barrier properties and light transmittance.

Benefits of technology

It realizes high barrier properties and light transmittance of biodegradable materials for catering, improves the freshness and fragrance preservation functions of film bags, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of degradable materials, and particularly relates to a degradable material for catering and a preparation method thereof. Raw materials of the degradable material comprise the following components in parts by weight: 50-90 parts of PBAT resin; 10 to 50 parts of PPCP resin; 5-30 parts of modified calcium carbonate; and 0.5-5 parts of a chain extender. The degradable material for catering disclosed by the invention has excellent light transmittance, barrier property and heat sealability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of degradable materials, and in particular relates to a degradable material for catering and a preparation method thereof. Background Art

[0002] With the improvement of global environmental awareness and the advancement of sustainable development, disposable degradable materials will become one of the important development directions in the field of plastic products in the future. Disposable plastic products are widely used, and the market size of degradable materials is gradually expanding. The application field of disposable degradable materials is very wide, not only limited to traditional disposable plastic products, but also expanded to agriculture, medical care, packaging and other fields. The demand for degradable materials has grown significantly. Biodegradable materials can be gradually degraded into water, carbon dioxide and biomass through the decomposition of microorganisms, becoming an effective means to solve plastic pollution.

[0003] As a biodegradable material, PBAT (polybutylene terephthalate) packaging film has many advantages, such as good film properties, excellent flexibility and biodegradability. PBAT is the main development direction of degradable materials in the future, so it is also widely used in the manufacture of disposable tableware, plastic bags and other degradable plastic products. However, the barrier properties of PBAT (polybutylene terephthalate) packaging film need to be improved, such as oxygen permeability and water vapor permeability, which are not ideal, which will affect its preservation effect as a packaging material. As the application scope of PBAT film expands, the requirements for its transparency are getting higher and higher. However, PBAT (polybutylene terephthalate) is a semi-crystalline polymer, and it is difficult to achieve a high light transmittance. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low barrier properties and low light transmittance of PBAT (polybutylene terephthalate adipate) packaging films in the prior art, and to provide a degradable material for catering and a preparation method thereof, wherein the degradable material for catering has both high barrier properties and light transmittance.

[0005] The first aspect of the present invention provides a degradable material for catering, wherein the raw materials of the degradable material include the following components in parts by weight: PBAT resin 50-90 parts; PPCP resin 10-50 parts; 5-30 parts of modified calcium carbonate; Chain extender 0.5-5 parts; Wherein, the preparation method of the modified calcium carbonate comprises: (1) adding calcium carbonate to a nitric acid solution, mixing, and then adding sodium 3-mercaptopropane sulfonate to carry out a first reaction, then filtering out a solid, and drying to obtain acidified calcium carbonate; (2) mixing an acrylic acid ester monomer, an initiator and a solvent and performing a second reaction to obtain a product material A; (3) taking acidified calcium carbonate, adding N,N-dimethylformamide, triethylamine and toluene-2,4-diisocyanate to carry out reflux reaction at 100-120° C. for 1-2 hours, then adding product material A to carry out reflux reaction at 140-150° C. for 40-60 minutes, then filtering out the solid, washing with water, and drying to obtain modified calcium carbonate.

[0006] At present, when PBAT resin is used in biodegradable materials for catering, its barrier property is not good, and some fillers are often added to increase its barrier property. The most commonly used filler is calcium carbonate. However, calcium carbonate has poor compatibility with the PBAT resin system. Not only can it not increase the barrier property of the final material well, but it also affects the transparency of the final material. In the present invention, the inventors have found that the use of the specific modified calcium carbonate in the present invention can not only better increase the barrier property of the material, but also basically does not affect the transparency of the material. This may be because the polydopamine coating of calcium carbonate enables the modified calcium carbonate to be better dispersed in the matrix, and the molecular chains formed by the interaction of the groups in the polyacrylate in the modified calcium carbonate and the groups in the PBAT resin and the PPCP resin can be interspersed between the molecules in the calcium carbonate, resulting in a more tortuous molecular diffusion path, thereby better increasing the barrier property of the material, and having almost no effect on the transparency of the material. Furthermore, the modified calcium carbonate can change the crystallization behavior of biodegradable polyester, accelerate the crystallization rate, increase the crystallization density, and promote the refinement of the grain size to increase the light transmittance.

[0007] Furthermore, in order to make the various components in the degradable material cooperate with each other better and make the degradable material have better performance, the raw materials of the degradable material include the following components in parts by weight: PBAT resin 65-75 parts; PPCP resin 25-35 parts; 15-20 parts of modified calcium carbonate; Chain extender 1-1.5 parts.

[0008] Furthermore, when preparing modified calcium carbonate, in step (1), the average particle size of the calcium carbonate is 0.1-5 microns, for example, 0.1 microns, 0.5 microns, 0.7 microns, 1 micron, 2 microns, 3 microns, 4 microns, and 5 microns.

[0009] The calcium carbonate in the present invention can be obtained from the market, and its preferred model is IMERYS calcium carbonate S, and its average particle size is 0.7 micrometer.

[0010] Furthermore, when preparing modified calcium carbonate, in step (1), the nitric acid solution is an aqueous nitric acid solution with a mass concentration of 60-80wt%.

[0011] Furthermore, when preparing modified calcium carbonate, in step (1), the mass ratio of the calcium carbonate, the nitric acid solution and the sodium 3-mercaptopropane sulfonate is (20-60):100:(0.1-1), preferably (40-50):100:(0.3-0.4).

[0012] Furthermore, when preparing modified calcium carbonate, in step (1), the mixing conditions include mixing at 40-50° C. for 30-50 minutes.

[0013] Furthermore, when preparing modified calcium carbonate, in step (1), the conditions for carrying out the first reaction include: reacting at 70-80° C. for 1-2 hours.

[0014] Furthermore, when preparing modified calcium carbonate, in step (1), the drying conditions are not particularly limited as long as the water can be removed. Preferably, the drying conditions include: drying at 100-120° C. for 3-6 hours.

[0015] Furthermore, when preparing modified calcium carbonate, in step (2), the acrylic acid ester monomer is selected from at least one of dopamine methacrylate, methyl methacrylate, styrene, butyl methacrylate and isooctyl acrylate.

[0016] Furthermore, the acrylic acid ester monomers are dopamine methacrylate and isooctyl acrylate, and preferably the weight ratio thereof is (4-8):1, for example, 4:1, 5:1, 6:1, 7:1, 8:1, and preferably (5-6):1.

[0017] In the present invention, the inventors have found through experimental research that the use of specific dopamine methacrylate and isooctyl acrylate can not only better increase the barrier properties of the material, but also better increase the heat sealing performance of the material. The experimental results show that this may be because the dopamine structure in dopamine methacrylate has better viscosity, and the structure of polyacrylate interacts with PBAT and PPCP, so that the contact surface of the material during the melting process has a strong interface interaction, thereby generating sufficient sealing strength.

[0018] Furthermore, when preparing modified calcium carbonate, in step (2), the initiator is selected from azobisisobutyronitrile and / or benzoyl peroxide, preferably azobisisobutyronitrile.

[0019] Furthermore, when preparing modified calcium carbonate, in step (2), the solvent is selected from at least one of N-methylpyrrolidone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and ethyl acetate, preferably N,N-dimethylformamide.

[0020] Furthermore, when preparing modified calcium carbonate, in step (2), the weight ratio of the acrylic ester monomer, the initiator and the solvent is 1: (0.01-0.1): (2-5), preferably 1: (0.03-0.05): (3-4).

[0021] Furthermore, when preparing modified calcium carbonate, in step (2), the mixing conditions are not particularly limited, and uniform mixing is sufficient, and the present invention will not elaborate on them in detail.

[0022] Furthermore, when preparing modified calcium carbonate, in step (2), the conditions of the second reaction include: reacting at 80-90° C. for 1-2 hours.

[0023] Furthermore, when preparing modified calcium carbonate, in step (3), the weight ratio of the acidified calcium carbonate, N,N-dimethylformamide, triethylamine, toluene-2,4-diisocyanate and the product material A is 1:(3-10):(0.5-1.2):(0.1-1):(15-30), preferably 1:(6-8):(0.6-0.8):(0.3-0.4):(18-20).

[0024] Furthermore, when preparing modified calcium carbonate, in step (3), the water washing method is a conventional operation method in the art, and generally the water washing can be performed multiple times, for example, 5-6 times. The operation method is not described in detail in the present invention.

[0025] Furthermore, when preparing modified calcium carbonate, in step (3), the drying conditions include: drying in a vacuum drying oven at 60-80° C. to constant weight.

[0026] Further, the value of the melt index of the PBAT resin at 190° C. and 2.16 kg is recorded as A, and the value of the glass transition temperature of the PPCP resin is recorded as B, wherein B / A=5-10, preferably 8-10.

[0027] In the present invention, the inventors of the present invention have found that the use of PBAT resin and PPCP resin satisfying B / A=5-10, preferably 8-10 can better increase the transparency of the material. This may be because the PBAT resin and PPCP resin within the above range can ensure good fluidity of the melt system during the preparation process of the material, and the PPCP resin can better regulate the crystallinity of the PBAT resin during the flow and subsequent crystallization process, and can form a smaller crystal form, thereby ensuring the light transmittance of the material.

[0028] Furthermore, the melt index of the PBAT resin at 190° C. and 2.16 kg is 4-6 g / 10 min, preferably 5 g / 10 min.

[0029] Furthermore, the model of the PBAT resin is PBAT THJS-7801 Xinjiang Lanshan Tunhe, and the melt index at 190° C. and 2.16 kg is 5 g / 10 min.

[0030] In the present invention, PPCP resin refers to a carbon dioxide-based polyester-polycarbonate terpolymer, which is a fully biodegradable plastic that can pass industrial composting and household composting certification. Its degradation performance is better than that of PLA, and it can significantly reduce costs, which is another great boost to the promotion of degradable products.

[0031] Furthermore, the glass transition temperature of the carbon dioxide based polyester-polycarbonate terpolymer is 30-50°C, for example, 30°C, 36.3°C, 40.5°C, 45.6°C, 47.4°C, 50°C.

[0032] Furthermore, in the PPCP resin: the content of polyester in the polymer is 10-40%, for example, 10%, 15%, 33%, 40%; the content of polyether in the polymer is less than 10%, for example, 2%, 3.6%, 4.9%, 5.8%, 8%, and the rest is polycarbonate content.

[0033] In the present invention, the content of each segment in the PPCP resin is obtained by nuclear magnetic resonance analysis and is a molar content.

[0034] Furthermore, the number average molecular weight of the PPCP resin is 50-120 kDa, for example, 50 kDa, 52.7 kDa, 61.2 kDa, 102 kDa, 110 kDa, and 120 kDa.

[0035] Furthermore, the PDI of the PPCP resin is 1.15-1.4, for example, 1.15, 1.18, 1.27, or 1.35.

[0036] Furthermore, the preparation method of the PPCP resin is prepared by referring to the preparation method in CN111378101A, specifically: monomers phthalic anhydride, propylene oxide, catalysts tetra-n-butylammonium chloride and triethyl boron are added to a high-pressure reactor, a third monomer carbon dioxide is charged, heating is carried out for a ternary ring-opening copolymerization reaction, and after the reaction is completed, the PPCP resin is obtained by precipitation, drying and granulation; wherein the molar ratio of tetra-n-butylammonium chloride to triethyl boron is 1:2-8; the molar feed ratio of tetra-n-butylammonium chloride to phthalic anhydride is 1:50-2000; the molar feed ratio of propylene oxide to phthalic anhydride is 1:2-30; the carbon dioxide pressure of the ring-opening copolymerization reaction is 0.1-3MPa, the reaction temperature is 40-100°C, and the reaction time is 4-15h.

[0037] Furthermore, the chain extender is selected from at least one of ADR-4368, ADR-4370, ADR-4400 and ADR-4468, preferably ADR-4400.

[0038] The second aspect of the present invention provides a method for preparing the above-mentioned degradable material for catering, the preparation method comprising: S1: adding PBAT resin, PPCP resin, modified calcium carbonate and chain extender into a high-speed mixer and mixing to obtain a mixture; S2 is prepared by feeding the mixed material into a twin-screw extruder for melting, extrusion and granulation.

[0039] Furthermore, when preparing the degradable material for catering, in step S1, the mixing condition is: 800-12000 r / min for 2-4 minutes.

[0040] Furthermore, when preparing biodegradable materials for catering, in step S2, the set temperatures of the twin-screw extruder are set to 145-155°C, 160-170°C, 170-180°C, 170-180°C, 180-190°C, 190-200°C, and 180-190°C from the feed port to the head, respectively.

[0041] Furthermore, the aspect ratio of the twin-screw extruder is 48, and the screw speed is 120-150 rpm.

[0042] The degradable material for catering in the present invention can be used in catering packaging, that is, the degradable material is made into a film product according to a conventional method in the art, for example, the degradable material for catering is prepared into a corresponding film product by extrusion blow molding, and the thickness of the film can be selected according to needs, for example, 40-100 microns. Specifically, the degradable material for catering is placed in a film blowing machine, the blowing temperature is 150-180°C, the blowing ratio is 3-6:1, and the die gap of the film blowing machine is 0.65-2.5mm.

[0043] Compared with the prior art, the present invention has at least the following beneficial effects: 1. Better economic value: The cost of PBAT resin is high. The synergistic effect of PPCP resin and PBAT resin used in the present invention can significantly reduce its cost, which is another great boost to the promotion of biodegradable products.

[0044] 2. Higher transparency: PPCP resin has excellent transparency, but PBAT resin is a semi-crystalline polymer, and calcium carbonate is an inorganic compound. It has poor compatibility in the system of PBAT resin and PPCP resin, resulting in a decrease in the transmittance of the final material. After extensive research, the inventors of the present invention found that the use of specific PBAT resin and PPCP resin synergistically and the use of specific modified calcium carbonate can make the biodegradable material for catering have a high transmittance.

[0045] 3. High barrier function: In the present invention, the specific modified calcium carbonate and PBAT resin and PPCP resin interact synergistically to make the degradable material for catering have high barrier properties, which can be used in film bag products to enhance the freshness and fragrance preservation functions of the film bag products.

[0046] 4. Better heat-sealing performance: The formula system of the biodegradable material film bag for catering in the present invention can improve the heat-sealing strength of the film bag products. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Example 1 This embodiment provides a degradable material for catering, the raw materials of which include the following components in parts by weight: 60 parts of PBAT resin; PPCP resin 25 parts; 18 parts of modified calcium carbonate; 1.2 parts of chain extender; The preparation method of modified calcium carbonate is: (1) adding calcium carbonate to a nitric acid solution, mixing, and then adding sodium 3-mercaptopropane sulfonate to carry out a first reaction, then filtering out a solid, and drying to obtain acidified calcium carbonate; (2) mixing an acrylic acid ester monomer, an initiator and a solvent and performing a second reaction to obtain a product material A; (3) adding N,N-dimethylformamide, triethylamine and toluene-2,4-diisocyanate to the acidified calcium carbonate for reflux reaction at 110° C. for 1.5 hours, then adding the product material A for reflux reaction at 145° C. for 50 minutes, then filtering the solid, washing with water, and drying to obtain the modified calcium carbonate; In step (1), the model of calcium carbonate is IMERYS calcium carbonate S, and its average particle size is 0.7 micrometer; the nitric acid solution is a nitric acid aqueous solution with a mass concentration of 70wt%; the mass ratio of calcium carbonate, nitric acid solution and sodium 3-mercaptopropane sulfonate is 45:100:0.35; the mixing conditions are: mixing at 35°C for 40 minutes; the first reaction condition is to react at 75°C for 1.5 hours; the drying condition is to dry at 110°C for 4 hours; In step (2), the acrylate monomer is dopamine methacrylate and isooctyl acrylate, and the weight ratio is 5:1; the initiator is azobisisobutyronitrile; the solvent is N,N-dimethylformamide; the weight ratio of the acrylate monomer, the initiator and the solvent is 1:0.05:3.8; the second reaction condition is 85°C for 1.5 hours; In step (3), the weight ratio of acidified calcium carbonate, N,N-dimethylformamide, triethylamine, toluene-2,4-diisocyanate and product material A is 1:7:0.7:0.35:18; washing with water 6 times; drying conditions are drying in a vacuum drying oven at 75° C. to constant weight; The model of PBAT resin is PBAT THJS-7801 Xinjiang Lanshan Tunhe, and the melt index at 190°C and 2.16kg is 5g / 10min; PPCP resin was prepared according to the method in Example 1 of CN111378101B, Mn=52.7 kDa, PDI=1.16, polyester content=14.8%, polycarbonate content=14.8%, polyether content=81.6%, Tg=40.5°C; The chain extender is ADR-4400; The method for preparing the degradable material for catering comprises: S1: adding PBAT resin, PPCP resin, modified calcium carbonate and chain extender into a high-speed mixer and mixing to obtain a mixture; S2 puts the mixed material into a twin-screw extruder for melting, extrusion and granulation to obtain; In step S1: the mixing condition is 1000 r / min for 3 minutes; In step S2: the set temperatures of the twin-screw extruder are set to 150°C, 165°C, 175°C, 175°C, 190°C, 195°C, and 185°C from the feed port to the die head; the aspect ratio of the twin-screw extruder is 48 and the screw speed is 140rpm.

[0049] Example 2 This embodiment provides a degradable material for catering, the raw materials of which include the following components in parts by weight: 75 parts of PBAT resin; PPCP resin 35 parts; 20 parts of modified calcium carbonate; 1 part of chain extender; The preparation method of modified calcium carbonate is: (1) adding calcium carbonate to a nitric acid solution, mixing, and then adding sodium 3-mercaptopropane sulfonate to carry out a first reaction, then filtering out a solid, and drying to obtain acidified calcium carbonate; (2) mixing an acrylic acid ester monomer, an initiator and a solvent and performing a second reaction to obtain a product material A; (3) adding N,N-dimethylformamide, triethylamine and toluene-2,4-diisocyanate to the acidified calcium carbonate for reflux reaction at 120° C. for 1 hour, then adding the product material A for reflux reaction at 150° C. for 40 minutes, then filtering the solid, washing with water, and drying to obtain the modified calcium carbonate; In step (1), the model of calcium carbonate is IMERYS calcium carbonate S, and its average particle size is 0.7 micrometer; the nitric acid solution is a nitric acid aqueous solution with a mass concentration of 70wt%; the mass ratio of calcium carbonate, nitric acid solution and sodium 3-mercaptopropane sulfonate is 50:100:0.4; the mixing conditions are: mixing at 40°C for 30 minutes; the first reaction condition is to react at 80°C for 1 hour; the drying condition is to dry at 110°C for 4 hours; In step (2), the acrylate monomer is dopamine methacrylate and isooctyl acrylate, and the weight ratio is 6:1; the initiator is azobisisobutyronitrile; the solvent is N,N-dimethylformamide; the weight ratio of the acrylate monomer, the initiator and the solvent is 1:0.03:4; the condition of the second reaction is 90° C. for 1 hour; In step (3), the weight ratio of acidified calcium carbonate, N,N-dimethylformamide, triethylamine, toluene-2,4-diisocyanate and product material A is 1:8:0.6:0.4:20; washing with water 6 times; drying conditions are drying in a vacuum drying oven at 75° C. to constant weight; The model of PBAT resin is PBAT THJS-7801 Xinjiang Lanshan Tunhe, and the melt index at 190°C and 2.16kg is 5g / 10min; PPCP resin was prepared according to the method in Example 2 of CN111378101B, Mn = 102.8 kDa, PDI = 1.35, polyester content = 39.9%, polycarbonate content = 55.2%, polyether content = 4.9%, Tg = 47.4°C; The chain extender is ADR-4400; The method for preparing the degradable material for catering comprises: S1: adding PBAT resin, PPCP resin, modified calcium carbonate and chain extender into a high-speed mixer and mixing to obtain a mixture; S2 puts the mixed material into a twin-screw extruder for melting, extrusion and granulation to obtain; In step S1: the mixing condition is 1200 r / min for 2 minutes; In step S2: the set temperatures of the twin-screw extruder are set to 155°C, 165°C, 175°C, 175°C, 185°C, 195°C, and 190°C from the feed port to the die head; the aspect ratio of the twin-screw extruder is 48 and the screw speed is 120rpm.

[0050] Comparative Example 1 The method according to Example 1 is different in that: IMERYS calcium carbonate S (whose average particle size is 0.7 μm) was used to replace the modified calcium carbonate, and the rest was the same as in Example 1, and finally a degradable material for catering was prepared.

[0051] Comparative Example 2 The method according to Example 1 is different in that: The acrylate monomer is isooctyl acrylate, and the rest is the same as in Example 1, and finally a degradable material for catering is prepared.

[0052] Comparative Example 3 The method according to Example 1 is different in that: The acrylate monomer is dopamine methacrylate, and the rest is the same as in Example 1, and finally a degradable material for catering is prepared.

[0053] Comparative Example 4 The method according to Example 1 is different in that: The acrylate monomers are dopamine methacrylate and styrene in a weight ratio of 5:1. The rest is the same as in Example 1, and finally a degradable material for catering is prepared.

[0054] Comparative Example 5 The method according to Example 1 is different in that: The preparation method of modified calcium carbonate is: Calcium carbonate was added to ethanol and mixed, and then a coupling agent KH570 was added to react at 70°C for 2 hours, and then the solid was filtered, washed with water, and dried to obtain modified calcium carbonate; The model of calcium carbonate is IMERYS calcium carbonate S, and its average particle size is 0.7 microns; the weight ratio of calcium carbonate, ethanol, and KH570 coupling agent is 1:10:0.07; washed with water 6 times; dried in a vacuum drying oven at 75°C to constant weight; the rest is the same as Example 1, and finally a biodegradable material for catering is prepared.

[0055] Comparative Example 6 The method according to Example 1 is different in that: The PBAT resin is 100 parts, the PPCP resin is 0 parts, and the PPCP resin is not added during the preparation; the rest is the same as in Example 1, and finally a biodegradable material for catering is prepared.

[0056] Comparative Example 7 The method according to Example 1 is different in that: The model of PBAT resin is PBAT JZHBM06 / Jinzhihong, and the melt index at 190° C. and 2.16 kg is 12 g / 10 min; the rest is the same as in Example 1, and finally a biodegradable material for catering is prepared.

[0057] Test Case The degradable catering materials in the embodiment and the comparative example were respectively placed in a film blowing machine, the blowing temperature was 170° C., the blowing ratio was 3:1, and the die gap of the film blowing machine was 0.65 mm. Finally, different films were prepared respectively, and the film thickness was 40 μm.

[0058] 1. Barrier properties: Oxygen permeability is tested according to GB / T 19789-2005, and water vapor permeability is tested according to GB / T1037-1988; 2. Light transmittance: tested in accordance with GB / T 2410-2008; 3. Heat seal strength: Heat seal strength test was carried out on a universal testing machine according to standard QB / T2358-1998, with a tensile speed of 300 mm / min.

[0059] The test results are shown in Table 1: Table 1 Test results

[0060] From the test results in Table 1, it can be seen that the degradable material for catering in the present invention has excellent light transmittance, barrier properties and heat sealing properties.

[0061] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A degradable material for catering, characterized in that: The raw materials of the degradable material include the following components by weight: PBAT resin 50-90 parts; PPCP resin 10-50 parts; 5-30 parts of modified calcium carbonate; Chain extender 0.5-5 parts; Wherein, the preparation method of the modified calcium carbonate comprises: (1) adding calcium carbonate to a nitric acid solution, mixing, and then adding sodium 3-mercaptopropane sulfonate to carry out a first reaction, then filtering out a solid, and drying to obtain acidified calcium carbonate; (2) mixing an acrylic acid ester monomer, an initiator and a solvent and performing a second reaction to obtain a product material A; (3) taking acidified calcium carbonate, adding N,N-dimethylformamide, triethylamine and toluene-2,4-diisocyanate to carry out reflux reaction at 100-120° C. for 1-2 hours, then adding product material A to carry out reflux reaction at 140-150° C. for 40-60 minutes, then filtering out the solid, washing with water, and drying to obtain modified calcium carbonate.

2. The degradable material according to claim 1, characterized in that: When preparing modified calcium carbonate, in step (1): the average particle size of the calcium carbonate is 0.1-5 microns The nitric acid solution is a nitric acid aqueous solution with a mass concentration of 60-80wt%; The mass ratio of the calcium carbonate, the nitric acid solution and the sodium 3-mercaptopropane sulfonate is (20-60):100:(0.1-1), preferably (40-50):100:(0.3-0.4); The conditions for the first reaction include: reacting at 70-80° C. for 1-2 hours.

3. The degradable material according to claim 1 or 2, characterized in that: When preparing modified calcium carbonate, in step (2): The acrylic acid ester monomer is selected from at least one of dopamine methacrylate, methyl methacrylate, styrene, butyl methacrylate and isooctyl acrylate; The initiator is selected from azobisisobutyronitrile and / or benzoyl peroxide; The solvent is selected from at least one of N-methylpyrrolidone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and ethyl acetate; The weight ratio of the acrylic acid ester monomer, the initiator and the solvent is 1:(0.01-0.1):(2-5); The conditions of the second reaction include: reacting at 80-90° C. for 1-2 hours.

4. The degradable material according to claim 1 or 2, characterized in that: When preparing modified calcium carbonate, in step (3): The weight ratio of the acidified calcium carbonate, N,N-dimethylformamide, triethylamine, toluene-2,4-diisocyanate and the product material A is 1:(3-10):(0.5-1.2):(0.1-1):(15-30).

5. The degradable material according to claim 1 or 2, characterized in that: The value of the melt index of the PBAT resin at 190° C. and 2.16 kg is recorded as A, and the value of the glass transition temperature of the PPCP resin is recorded as B, wherein B / A=5-10.

6. The degradable material according to claim 1 or 2, characterized in that: The PBAT resin has a melt index of 4-6 g / 10 min at 190° C. and 2.16 kg.

7. The degradable material according to claim 1 or 2, characterized in that: The glass transition temperature of the carbon dioxide-based polyester-polycarbonate terpolymer is 30-50° C.; the number average molecular weight of the PPCP resin is 50-120 kDa; and the PDI of the PPCP resin is 1.15-1.

4.

8. The degradable material according to claim 1 or 2, characterized in that: In the PPCP resin, the content of polyester in the polymer is 10-40%, the content of polyether in the polymer is less than 10%, and the rest is polycarbonate.

9. A degradable material for catering according to any one of claims 1 to 8, characterized in that: The preparation method comprises: S1: adding PBAT resin, PPCP resin, modified calcium carbonate and chain extender into a high-speed mixer and mixing to obtain a mixture; S2 is prepared by feeding the mixed material into a twin-screw extruder for melting, extrusion and granulation.

10. The preparation method according to claim 9, characterized in that: In step S2, the set temperatures of the twin-screw extruder are set to 145-155°C, 160-170°C, 170-180°C, 170-180°C, 180-190°C, 190-200°C, and 180-190°C from the feed inlet to the die head; the aspect ratio of the twin-screw extruder is 48 and the screw speed is 120-150rpm.

Citation Information

Cited By

  • Polycarbonate lamination material with high sealing strength

    CN120331059A